Online ad auctions: An experiment - Kevin McLaughlin; Daniel Friedman (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
A human subject laboratory experiment compares the real-time market performance of the two most popular auction formats for online ad space, Vickrey- Clarke-Groves (VCG) and Generalized Second Price (GSP). Theoretical predictions made in papers by Varian (2007) and Edelman et al. (2007) seem to organize the data well overall. Efficiency under VCG exceeds that under GSP in nearly all treatments. The difference is economically significant in the more competitive parameter configurations and is statistically significant in most treatments. Revenue capture tends to be similar across auction formats in most treatments.
Keywords: C92; D44; L11; L81; M3; 330; Laboratory Experiments; Auction; Online Auctions; Advertising